Al-Dharurah al-Syi’riyyah dalam Nadhom ‘Imrithi Karya Syekh Syarafuddin Yahya - Firdaus, Farhan (Nady Al-Adab : Jurnal Bahasa Arab, 2025)
Nazham  ‘imrithy is one of the nazham  which discusses the rules of Arabic sentence structure in poetic form. Even though it contains Arabic language rules, because it is presented in poetic form, it does not rule out the possibility of a clash between the language rules and the rules of ‘arudh science. The aim of this research is to find out the poetic necessity that exists in nazham  ‘imrithy The research method used is descriptive-analysis, while the data collection technique uses documentary data collection techniques by reading and taking notes. The results of this research are that there are poetic necessity that occur in several stanzas in nazham  ‘imrithy with the provisions; changed the ism ghairu munsharif (صرف ما لا ينصرف), shortened the long sound (قصر الممدود), replaced hamza washl with hamza qath’' (قطع همزة الوصل), replaced hamza qath’ with hamza washl (وصل همزة القطع), alleviete the hamza (تخفيف الهمزة), giving harokat to plural meem (تحريك ميم الجمع), giving harokat kasroh at the end of the majzum mudhari’i with sukun (تحريك آخر المضارع المجزوم بالسكون لأجل الروي), turning off the vowels (تسكين المتحرك), and turning on the consonants (وتحريك الساكن).   Keywords: arabic poetry, nazham  ‘imrithy, poetic necessity